Effect of Phosphorus Solublizing Bacteria (PSB) on Growth and Yield in Tomato - M K Poonia (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
A field experiment was conducted to study the effect of phosphate solublizing bacteria (PSB) on growth and yield of tomato. PSB culture was applied through soil and seedling root dip before transplanting with two levels of phosphorus fertilizers, i.e., 75% and 100% of recommended P, and compared. Results revealed that application of 100% P with seedling dip in PSB 1:10 solution recorded significantly higher plant height (86.30cm), leaf area index (3.52), number of fruits/plant (16.32), fruit weight (77.75g), fruit yield/plant (1125g) and yield (392.26 q/ha) compared to other treatment combinations, except 100% P with 5kg/ha soil application of PSB. The same treatment also recorded the highest (3.41) cost:benefit ratio. However, no significant difference was noticed in 100% recommended P with seedling dip in PSB solution, or soil application.